2018
DOI: 10.1136/bmjopen-2018-023051
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the urinary dipstick test in the management of patients with urinary tract infection-associated symptoms in primary care in Indonesia: a cross-sectional study

Abstract: ObjectiveTo assess the test characteristics of a urine dipstick test in predicting a positive urine culture in an outpatient setting in Indonesia.DesignCross-sectional study.SettingTwo outpatient clinics in Medan, Indonesia.Participants616 consecutively enrolled participants suspected of having a urinary tract infection.Outcome measuresThe primary outcome is the estimates of accuracy (sensitivity, specificity, predictive values) where urine culture is the reference test. The secondary outcome is the post-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The exclusion of UTIs enables healthcare professionals to focus on investigating and addressing other potential conditions, leading to improved patient care and a reduction in unnecessary antibiotic usage (Flokas et al 2017;Childers et al 2022). A similar study suggested that urine dipstick should follow a rule-out strategy as a negative dipstick test is indicative of a low probability of a positive urine culture, making the diagnosis of UTI unlikely, thus reducing the number of samples for culture and the use of empirical antimicrobial therapy (Ginting et al 2018). This study finding reports a high NPV of the urine dipstick, supporting this strategy for setting where culture can be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of UTIs enables healthcare professionals to focus on investigating and addressing other potential conditions, leading to improved patient care and a reduction in unnecessary antibiotic usage (Flokas et al 2017;Childers et al 2022). A similar study suggested that urine dipstick should follow a rule-out strategy as a negative dipstick test is indicative of a low probability of a positive urine culture, making the diagnosis of UTI unlikely, thus reducing the number of samples for culture and the use of empirical antimicrobial therapy (Ginting et al 2018). This study finding reports a high NPV of the urine dipstick, supporting this strategy for setting where culture can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The urine dipstick is the sole diagnosis method and an indication to start antibiotic treatment (Rousham et al 2019). The rule-in strategy could lead to reduced antimicrobial use compared to clinical diagnosis, where only signs and symptoms are used as criteria to start treating UTI (Ginting et al 2018). This practice, however, has the potential to overuse antibiotics, fostering the emergence of bacterial strains, reducing the effectiveness of crucial antibiotics as culture is not performed, and treating patients according to antibiotic susceptibility results (Rousham et al 2019;Ginting et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Dutch guidelines, for instance, indicate that a positive nitrite test in symptomatic females strongly suggests a UTI (6). Prompt treatment of UTIs is crucial to prevent complications such as renal insufficiency and end-stage renal disease (9,10). In cases where dipstick results indicate a suspected UTI, initiating empirical antibiotic therapy while awaiting culture results is a common practice (2).…”
Section: Introductionmentioning
confidence: 99%
“…The urine test is an indispensable preliminary examination performed during the diagnosis of many diseases ( 12 , 13 ). Leukocyte esterase detection during a routine urine examination is considered to be moderately sensitive and specific for detecting the presence of urinary tract infections ( 14 ), and the LET can also be used to screen for CT and NG infection ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%